Labor Market and Its Features in Modern Condition; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Marchuk V. I. Veronika Ivanovna; Suzdalova M. A. Marina Anatolievna; Nesteruk D. N. Dmitry Nikolaevich; Kvashnina D. A. Daria Aleksandrovna (2017, 2017)
Title screen